Ultrafast Porous Carbon Activation Promises High‐Energy Density Supercapacitors. Issue 23 (12th May 2022) - Liu, Zhedong; Duan, Cunpeng; Dou, Shuming; Yuan, Qunyao; Xu, Jie; Liu, Wei‐Di; Chen, Yanan
Abstract: Activated porous carbons (APCs) are traditionally produced by heat treatment and KOH activation, where the production time can be as long as 2 h, and the produced activated porous carbons suffer from relatively low specific surface area and porosity. In this study, the fast high‐temperature shock (HTS) carbonization and HTS‐KOH activation method to synthesize activated porous carbons with high specific surface area of ≈843 m 2 g ‐1, is proposed. During the HTS process, the instant Joule heating (at a heating speed of ≈1100 K s ‐1 ) with high temperature and rapid quenching can effectively produce abundant pores with homogeneous size‐distribution due to the instant melt of KOH into small droplets, which facilitates the interaction between carbon and KOH to form controllable, dense, and small pores. The as‐prepared HTS‐APC‐based supercapacitors deliver a high energy density of 25 Wh kg ‐1 at a power density of 582 W kg ‐1 in the EMIMBF4 ionic liquid. It is believed that the proposed HTS technique has created a new pathway for manufacturing activated porous carbons with largely enhanced energy density of supercapacitors, which can inspire the development of energy storage materials. Abstract : The coconut shell, characterized by loose structure and high carbon content, is employed to synthesize activated porous carbon by high‐temperature shock (HTS) progress. The instant Joule heating (at a heating speed of ≈1100 K s –1 ) with high temperature and rapid quenching facilitates the interaction between carbon and KOH to form controllable, dense, and small pores.